1987
DOI: 10.1111/j.1399-3054.1987.tb06155.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss and recovery of nitrogenase in Abuts incana nodules exposed to low oxygen and low temperature

Abstract: The possibility that respiration limits oxygen access to nitrogenase was tested by artificially upsetting the balance between oxygen consumption (respiration) and oxygen influx (diffusion). Argon treatment of the nodulated root system on intact plants stopped in vivo nitrogenase activity almost completely. Upon return to air, nitrogenase activity was very low and recovered gradually to full activity after about 5 h. In vitro measurements on nodule homogenates indicated that active nitrogenase was lost upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, if decreased activity in vivo was caused by lack of active nitrogenase, low activity would also be expected in vitro. In all cases nitrogenase activity in vivo and in vitro decreased almost in parallel when the plants were exposed to various stress factors (Huss-Danell & Sellstedt, 1985;Sundstrom & Huss-Danell, 1987;Huss-Danell, Winship & Hahlin, 1987;Huss-Danell & Hahlin, 1988;Vikman et al, 1990;Lundquist & Huss-Danell, 1991a, b). The loss of nitrogenase activity in vivo was apparently not restored by a supply of energy and reductant in vitro, and the interpretation is therefore that loss of active nitrogenase had occurred.…”
Section: Environmental Effects At the Plant Cell And Protein Levelmentioning
confidence: 89%
See 1 more Smart Citation
“…On the other hand, if decreased activity in vivo was caused by lack of active nitrogenase, low activity would also be expected in vitro. In all cases nitrogenase activity in vivo and in vitro decreased almost in parallel when the plants were exposed to various stress factors (Huss-Danell & Sellstedt, 1985;Sundstrom & Huss-Danell, 1987;Huss-Danell, Winship & Hahlin, 1987;Huss-Danell & Hahlin, 1988;Vikman et al, 1990;Lundquist & Huss-Danell, 1991a, b). The loss of nitrogenase activity in vivo was apparently not restored by a supply of energy and reductant in vitro, and the interpretation is therefore that loss of active nitrogenase had occurred.…”
Section: Environmental Effects At the Plant Cell And Protein Levelmentioning
confidence: 89%
“…This, in turn, would temporarily lower the rate of Og consumption until a new balance between incoming Og and consumed Og is reached. Short-term experiments with different oxygen tensions at normal (Rosendahl & Huss-Danell, 1988) or low temperature (Huss-Danell et al, 1987), and detailed studies on Ng/Ar shifts combined with different oxygen tensions (Lundquist, 1993), showed that the oxygen balance is involved in maintaining stable nitrogenase activity in Alnus. Growth experiments at different oxygen tensions (Silvester et al, 1988«;Kleemann et al, 1994) showed that, with time, Alnus nodules can adapt to altered oxygen tensions by altering the properties of Frankia vesicle envelopes as new vesicles are formed.…”
Section: Environmental Effects At the Plant Cell And Protein Levelmentioning
confidence: 99%
“…Several experiments performed on alders grown under controlled conditions have shown that different levels of stress affect the symbiosis differently. In a situation of moderate stress, as a short time exposure to low but not freezing temperature, the recovery is fairly fast (a few hours) and is probably mainly due to synthesis or reactivation of nitrogenase (Huss-Danell, Winship & Hahlin 1987). In a situation of severe stress, such as prolonged darkness (Lundquist & Huss-Danell 1991a,b;Vikman, Lundquist & Huss-Danell 1990), drought (Sundstrom & Huss-Danell, 1987), or chilling temperatures (Vogel & Dawson 1991), the recovery is slower, 5-7 d. Keeping alders in prolonged darkness resulted in a gradual loss of in vivo and in vitro nitrogenase activity as well as nitrogenase protein (Lundquist & Huss-Danell 1991a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fixation also appears to be temperature dependent. Optimal temperature for induction of Frankia nitrogenase activity in vitro or inside root nodules of actinorhizal plants is also well-documented (Reddell et al 1985;Fontaine et al 1986;Huss-Danell et al 1987;Tjepkema and Murry 1989). Frankia strain CpI1 exhibited maximum acetylene reduction activity and vesicle numbers at 25-30 °C temperature range (Tjepkema et al 1981;Tisa and Ensign 1987a).…”
Section: Temperature Tolerancementioning
confidence: 96%